Ways to improve the financial condition of Ukrainian banks - Zakharina, Yelyzaveta; Harkusha, Olena O. (My University, 2020)
Due to the beginning of hostilities in the Donbas region, the general crisis and significant devaluation of the national currency, the financial state of the banking systems of Ukraine has worsened. Theses show us measures that may be the basis for the rehabilitation program of the banking system of Ukraine. The financial condition of our country is important and very dependent on banks. That is why the analysis and search for ways to improve the current state of the banking system was conducted. Через початок бойових дій на Донбасі, загальну кризу та значну девальвацію національної валюти, погіршився фінансовий стан банківських систем України. Тези показують нам заходи, які можуть бути основою для програми реабілітації банківської системи України. Фінансовий стан нашої країни важливий і дуже залежить від банків. Саме тому було проведено аналіз та пошук шляхів покращення сучасного стану банківської системи.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; banking system; crisis; rehabilitation program; банківська система; програма реабілітації; криза